THE PRAGMATIC PHILOSOPHY: COMPUTER MEDIATED COMMUNICATION (CMC) IN ARABIC LANGUAGE LEARNING - Mohammad Shohibul Anwar; Wildana Wargadinata; M. Holil; Rodiatul Maghfiroh; Maulidi Maulidi (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2026)
This study explores the conceptual relationship between Pragmatism and Computer-Mediated Communication (CMC) within the context of Arabic language education. Pragmatism emphasizes the practical value of knowledge, aligning with the objective of Arabic instruction to develop communicative competence. CMC, particularly through Synchronous (SCMC) and Asynchronous (ACMC) modes, serves as a modern pedagogical tool to support language learning. This research adopts a literature-based approach by analyzing current academic sources to evaluate how CMC can enhance Arabic language acquisition through collaborative and contextual interaction. The findings suggest that effective integration of CMC can significantly improve students' proficiency, especially in a digital learning environment. The study offers valuable insights for developing innovative Arabic language teaching strategies that are aligned with pragmatic educational goals.